2019
DOI: 10.17583/qre.2019.3947
|View full text |Cite
|
Sign up to set email alerts
|

Question Asking and the Common Good: A Hermeneutic Investigation of Student Questioning in Moral Configurations of Classroom Practice

Abstract: This qualitative study (based on a hermeneutic moral-realist interpretive frame (Yanchar & Slife, 2017)) explored question asking as it unfolded in the everyday practice of being a student in a graduate course on design thinking (with an emphasis on design in education). Findings are presented as four key tensions that occurred within the complex classroom setting under investigation: “theory and overlapping practices,” “convergence and divergence,” “participation and reticence,” and “give and take.” Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Students should be encouraged participate more in asking questions to the teacher to create balance in the learning process (Gong and Yanchar, 2019).…”
Section: The Development Of Students' Answers Into a Rich Discussionmentioning
confidence: 99%
“…Students should be encouraged participate more in asking questions to the teacher to create balance in the learning process (Gong and Yanchar, 2019).…”
Section: The Development Of Students' Answers Into a Rich Discussionmentioning
confidence: 99%
“…One example of this strategy was offered in a study of graduate student question-asking in the classroom, conducted by a doctoral student and myself Yanchar & Gong, 2020). Mainstream psychological and educational research in this area is overwhelmingly cognitive, logocentric, and quantitative in nature, typically producing thin descriptions of representational structures, computational procedures, and taxonomies (for more details, see Gong, 2018). Our goal was to look at this phenomenon differently, that is, in a way that illuminated (in some measure) what has been obscured in traditional studies based on information processing and related assumptions.…”
Section: Direct Subversion Using An Explicit Theoretical Frameworkmentioning
confidence: 99%
“…But qualitative approaches designed to explore the meaning of human experience and phenomena, such as forms of hermeneutic (Fleming et al, 2003; Packer & Addison, 1989; Stigliano, 1989; Yanchar & Slife, 2017) and phenomenological (Giorgi & Giorgi, 2003; Wertz, 2005) inquiry, would seem to offer suitable methodological resources in this regard. For example, one recent hermeneutic study of student question asking in a graduate course suggested that concern and control were often connected with how, or whether, students asked questions in class (Gong & Yanchar, 2019). While the explicit topic of this study was student question asking as a kind of moral–educational practice, and the term “control” was not explicitly mentioned, the relevance of control became clear as some participants tended to dominate class time through their questions while others felt a kind of duty to avoid such domination or sought a balance between exerting too much and too little control over class discussion.…”
Section: Control Revisitedmentioning
confidence: 99%
“…Moreover, how some students tended to control discussions—often in indirect, subtle, or even tacit ways—was connected with what mattered in regard to their professional and personal aspirations; and what mattered was often complex and multifaceted, leading to complex class interactions. In these ways, this study (Gong & Yanchar, 2019) offered a novel account of student control via question asking in the classroom.…”
Section: Control Revisitedmentioning
confidence: 99%